Obesity and infectious diseases: pathophysiology and epidemiology of a double pandemic condition - Pugliese, Gabriella; Liccardi, Alessia; Graziadio, Chiara; Barrea, Luigi; Muscogiuri, Giovanna; Colao, Annamaria (International Journal of Obesity, 2022)
The current pandemic due to widespread SARS-CoV-19 infection has again highlighted the role of obesity, whose global prevalence increased up to 13%, as a risk factor for both susceptibility to infections and the occurrence of a more severe disease course. To date, this association has not been sufficiently explored. Obesity-related susceptibility to infectious diseases is mostly thought to be due to an impairment of both innate and adaptive immune responses and vitamin D deficiency. Several cofactors can indirectly favour the onset and/or worsening of infectious diseases, such as impairment of respiratory mechanics, skin and subcutaneous tissue homoeostasis, obesity-related comorbidities and inappropriate antimicrobial therapy. Subjects with obesity have a higher incidence of cutaneous infections, probably due to changes in skin barrier functions and wound healing. Excess weight is also associated with an increased risk of urinary tract infection and its recurrence, as well as with a higher prevalence of both lower and higher respiratory tract infections. Moreover, patients with obesity appear to have an increased risk of surgical site infections when undergoing general, orthopaedic, gynaecological, and bariatric surgery. Data concerning the different infectious diseases related to obesity are rather limited since anthropometric parameters are usually poorly recorded. Furthermore, specific therapeutic protocols in subjects with obesity are lacking, especially regarding antibiotic therapy and further supplements. This review summarizes etiopathogenetic and epidemiological evidence and highlights areas of uncertainty in the field of infectious diseases and obesity, which require further research. It is important to raise public awareness of this additional risk related to obesity and to raise awareness among the scientific community to develop specific clinical protocols for subjects with obesity.